An innovative efficient oxygen electrode for SOFC: Pr6O11 infiltrated into Gd-doped ceria backbone. (14th September 2016) - Nicollet, Clément; Flura, Aurélien; Vibhu, Vaibhav; Rougier, Aline; Bassat, Jean-Marc; Grenier, Jean-Claude
Abstract: The praseodymium oxide, Pr6 O11, is regarded as a potential electrocatalyst for the oxygen reduction reaction. Its mixed conductivity properties are characterized. At 600 °C the oxygen diffusion coefficient value is as high as 3.4 × 10 −8  cm 2  s −1, and that of the surface exchange coefficient is 5.4 × 10 −7  cm s −1, which supposes excellent electrocatalytic properties. The measured electronic conductivity is high enough for using this material as a SOFC cathode. Herein, praseodymium nitrate is infiltrated into Gd doped ceria (GDC) backbone and fired at 600 °C to form a composite oxygen electrode Pr6 O11 /GDC. Electrochemical measurements show very low polarization resistance, R p = 0.028 Ω cm 2 at 600 °C. A single cell made of a commercial Ni-YSZ/YSZ half cell and of the infiltrated cathode is able to deliver a maximum power density of 825 mW cm −2 at 600 °C. Ageing of this cell for 840 h, at 600 °C and 0.5 A cm −2, shows a degradation rate lower than 1%. Highlights: The Praseodymium oxide, Pr6 O11, shows quite high oxygen diffusion and surface exchange coefficients. It is an excellent electrocatalyst for the oxygen reduction reaction in SOFC cathode. Infiltrated into a GDC backbone leads to a cathode showing very low polarization resistance. A single cell with this cathode exhibits a power density as high as 0.825 W cm −2 at 600 °C. Ageing test over 840 h shows a degradation rate lower than 1% per 1000 h.